2013
DOI: 10.1590/s0100-06832013000400023
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas e químicas em diferentes usos do solo no Brejo Paraibano

Abstract: RESUMOA substituição da vegetação nativa no Brejo Paraibano, inicialmente por canade-açúcar e mais recentemente por pastagens, em relevo fortemente ondulado, causaram sérios problemas de degradação do solo. Atualmente, partes dessas pastagens estão dando lugar ao plantio de sabiá (Mimosa caesalpiniaefolia Benth). Objetivou-se, neste trabalho, analisar o efeito dessas mudanças nas propriedades físicas e químicas do solo e no desenvolvimento das raízes. O experimento foi conduzido no município de Areia, PB, em u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
0
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
(35 reference statements)
3
0
0
8
Order By: Relevance
“…4/8 0.10 m layer; higher microporosity and lower soil density than the agropastoral and no-tillage systems in the superficial layer (0-0.05 m); higher percentage of aggregates larger than 2 mm and higher WMD than the agropastoral and no-tillage systems in the 0.10-0.20 m layer; higher microporosity than pasture, agropastoral and no-tillage systems, and higher percentage of aggregates larger than 2 mm than the agropastoral and no-tillage systems in the 0.20-0.40 m layer. These results corroborate with Diel et al (2014), who also observed higher organic matter content in the area under native forest; also with Silva et al (2013), who found higher WMD in the area under forest; and with Silva et al (2015), who found lower soil density values in forested soils used as a reference, also emphasizing that anthropic use increases soil compaction.…”
Section: Resultssupporting
confidence: 89%
“…4/8 0.10 m layer; higher microporosity and lower soil density than the agropastoral and no-tillage systems in the superficial layer (0-0.05 m); higher percentage of aggregates larger than 2 mm and higher WMD than the agropastoral and no-tillage systems in the 0.10-0.20 m layer; higher microporosity than pasture, agropastoral and no-tillage systems, and higher percentage of aggregates larger than 2 mm than the agropastoral and no-tillage systems in the 0.20-0.40 m layer. These results corroborate with Diel et al (2014), who also observed higher organic matter content in the area under native forest; also with Silva et al (2013), who found higher WMD in the area under forest; and with Silva et al (2015), who found lower soil density values in forested soils used as a reference, also emphasizing that anthropic use increases soil compaction.…”
Section: Resultssupporting
confidence: 89%
“…De modo geral, os menores valores de nutrientes nos solos foram encontrados sob mata e sob cultivo convencional (Tabela 2), o que em parte se explicam pelo fato de que nos solos sob mata a maioria dos nutrientes está alocada na vegetação (SILVA et al, 2013) e, no cultivo convencional, devido a, possivelmente, ausência de práticas de manejo que favoreçam a manutenção e/ou melhoria da fertilidade do solo, como a adição de matéria orgânica e a reposição dos nutrientes exportados pelas produções das culturas cultivadas e/ou perdidos pela erosão e lixiviação.…”
Section: B ----------------------------------------------------------unclassified
“…(Lazzaretti et al, 2019). As condições físicas do solo como agregação e estabilidade de agregados, textura, grau de floculação de argila, densidade do solo e porosidade também são de suma importância, pois influenciam no crescimento e desenvolvimento do sistema radicular das plantas e na capacidade de infiltração de água no solo e consequentemente, o solo se torna mais resistente ao processo erosivo e a degradação (Borchartt, 2013;Brandão et al, 2006& Costa et al, 2004. Rampim et al, (2020) ficaram evidentes os efeitos positivos da adoção de mais de um método de manejo, modificando os atributos físicos, como menor densidade do solo e resistência a penetração, e maior macroporosidade, aprimorando a qualidade do solo, com reduzida interferência na produtividade agrícola.…”
Section: Introductionunclassified